Optimalisasi Penggunaan Dana Desa Membawa Desa Kutuh-Badung-Bali Menjadi Smart Village - Amalia Syauket; Ratna Indriasari (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2024)
The development of rural areas through the application of the smart village concept is inseparable from the support of information and communication technology. Kutuh-Bali Village is a village that is able to understand the problems and able to organize its resources to solve existing problems and optimize its potential so that its residents feel comfortable, safe, and become an independent village in Indonesia. Qualitative research description with case study type, aims to determine the optimization of the use of village funds in Kutuh Village Bali to become a smart village with the application of smart governance components. By using multiple sources such as interviews, observations and the use of secondary data sources since 2020. Research result the village fund obtained every year has been managed very well in a harmonious relationship between the perbekel and bendese adat and is used optimally by building a Village Information System (SID) part of the implementation of e-government which is a tool for the village to manage village data such as village administration, correspondence management, and village population data management. and the Siskeudes application as a fraud mitigation in the use of village funds, in accordance with the priorities of village development and based on village development priorities and based on village authority as a form of implementation of the Tri Hitna Karana philosophy.